Kata Serapan Pada Terjemahan Takarir Film Marriage Story - M Iqbal Farhan Zhovran (PENAOQ: Jurnal Sastra, Budaya dan Pariwisata, 2022)
Subtitle used in the movie for helping the audience understand the movie conversation, usually in the country that have a different language with the country which produce the movie. The translator ussually use the loanwords for help the audience understand the conversation easily. In this study, the authors will analyze the loanwords in the subtitle titled “Kata Serapan Pada Terjemahan Takarir Film Marriage Story”. This study aims at loanword strategy in subtitle the translation on Marriage Story dan the effect to audience. To analyze the loanwords strategy authors using a translation theory and loanwords theory. This study using descriptive and qualitative methods and the collecting data technique with teknik simak libat cakap, teknik rekam, and teknik catat method. The result of study that there are just two from three kind of loanwords, there are alternation change 6,25% and phonetic and phonemic change 93,75%. Moreover, authors found the positive and negative effect that happened to audiemce by the loanwords on the subtitle, there are increasimg the vocabullary for the audience. And for the negative effect, the audience is not understand the loanwords using, because it unsually word that they always do on daily.